The Increase in Container Capacity at Slovenia's Port of Koper - Marko Perkovic (TransNav: International Journal on Marine Navigation and Safety of Sea Transportation, 2013)
The ports of the northern Adriatic are ranged in three countries, Koper's being the only one in Slovenia and therefore of distinctive import to the country, which with its limited coastal space has no other options for expanding maritime trade than increasing the capacity of this one extant port. The state of Slovenia is the largest shareholder and the future development of the port depends on decisions made by the Ministry of Infrastructure. The increase in container throughput in the Port of Koper requires a reconstruction and extension of the current container terminal as an absolute priority. Regarding economic sustainability the extension must be in line with the estimated growth of traffic as well as with the exploitation of present and future terminal capacities. The occasional expansion projects must fulfil environmental and safety requirements. For large container vessels (LOA more than 330 m) calling at the Port of Koper the safety of the berthing and departure conditions have to be simulated under various metocean conditions. At the same time manoeuvres should not be intrusive – expected propeller wash or bottom wash phenomena must be analysed. When large powerful container vessels are manoeuvring in shallow water bottom wash is expected and because sediments at the port are quite contaminated with mercury some negative environmental influence is expected. The most important expected investment in the container terminal is therefore extending (enlarging) and deepening the berth. The paper will present statistics and methods supporting container terminal enlargement and a safety and environmental assessment derived from the use of a ship handling simulator.